The Paradigm of Parāvidyā-Aparāvidyā the Hindu Contribution to the Future Development of Science - Donder, I Ketut; Suwantana, I Gede; Chakravortti, Sudip; Subawa, I Made Pasek; Witana, I Nyoman (Journal of Cultural Analysis and Social Change, 2025)
This study examines the Parāvidyā and Aparāvidyā paradigms within Hindu tradition and their contributions to the development of knowledge in the future. Parāvidyā, the highest form of knowledge that transcends the worldly aspects, offers a spiritual and ethical dimension that can enrich modern scientific approaches. On the other hand, Aparāvidyā, as worldly knowledge that focuses on understanding the universe, remains relevant in the context of technological and scientific advancements. This research integrates a literature review of classical Hindu texts and a discourse analysis on the application of these two paradigms in contemporary knowledge and technology development. The findings indicate that, although the two concepts focus on different fields, they complement each other and provide a holistic view in addressing global challenges such as climate change and technological progress. The Parāvidyā-Aparāvidyā paradigm offers a more balanced model of knowledge between material progress and spiritual well-being, which can promote the development of more ethical and responsible science. Thus, the Hindu tradition provides an important contribution to the future of knowledge by proposing an approach that integrates both worldly and spiritual knowledge to achieve sustainability and human welfare.